2020
DOI: 10.1177/1071100720962480
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Site Vancomycin Powder Application in Infected Diabetic Heel Ulcers With Calcaneal Osteomyelitis

Abstract: Background: Intraoperative site application of vancomycin powder has been found to be beneficial in foot and ankle surgery among diabetic patients undergoing elective procedures. However, there are concerns for risks such as selection of multidrug-resistant bacteria, local tissue irritation, and increased wound complications. The clinical utility of intraoperative site vancomycin powder application in infected diabetic foot ulcer surgery is unknown. We aimed to report the clinical outcomes of partial or total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…The use of topical antibiotic therapy is controversial in the setting of osteomyelitis treatment. Traditionally, antibiotic-eluting beads have been used as a local antibiotic delivery source with variable effects on treatment outcomes depending on the anatomical location examined [168][169][170] . The twostage exchange for PJI, with a first-stage placement of an antibiotic eluting spacer, is considered the standard of care for chronic PJI; however, the necessity of the antibiotic elution from the spacer versus limb support and treatment of dead space (empty space from excised tissue) remains controversial.…”
Section: Synovial Fluidmentioning
confidence: 99%
“…The use of topical antibiotic therapy is controversial in the setting of osteomyelitis treatment. Traditionally, antibiotic-eluting beads have been used as a local antibiotic delivery source with variable effects on treatment outcomes depending on the anatomical location examined [168][169][170] . The twostage exchange for PJI, with a first-stage placement of an antibiotic eluting spacer, is considered the standard of care for chronic PJI; however, the necessity of the antibiotic elution from the spacer versus limb support and treatment of dead space (empty space from excised tissue) remains controversial.…”
Section: Synovial Fluidmentioning
confidence: 99%
“…Infection will lead to painful wound, a sign which should be carefully evaluated especially in diabetic patients. In our study 71.67% had pain on wounds while 28.33% did not had painful wound [19][20][21] . Swelling around the wound is expected initially but if it is associated with un-usual pain or fail to subside over certain time period, infection must be ruled out 22,23 .…”
Section: Discussionmentioning
confidence: 43%
“…Glucosuria is high level of sugar in urine which can lead to renal function compromise because kidneys have to filter out high glucose levels. DM also alter the carbohydrate metabolism in the body which leads to these systemic complications 21,26 . Diabetic ketoacidosis is a dangerous escalation of uncontrolled blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the local use of antibiotics has been widely used in practice. Multiple clinical studies have reported a good effect of VCSI in the treatment of chronic osteomyelitis [ 9 , 10 ]. The primary objective of this retrospective study was to compare the efficiency of FD and VCSI in the treatment of sclerosing osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%